Estudo termodinâmico, microrreológico e de propriedades mecânicas de blendas poliméricas ternárias com matriz de PCL - Valio, Gustavo Trindade (2020)
There is a demand for high quality materials that meet specific needs such as comfort, low cost and direct skin molding for making orthoses. This work aimed develop and identify some mechanical properties and the microrheology of a possible blend for this purpose. Ternary blends with Poly (ε-caprolactone) (PCL) matrix and Poly (butyral vinyl) (PVB) and Ethylene-Vinyl Acetate (EVA) copolymer (EVA) as dispersed phases were elaborated. Therefore, PCL is used by all commercial products because it has a low melting temperature (60 ° C). The use of PVB was proposed in an attempt to generate a shape memory blend, an important property during the making and molding. EVA was used in an attempt to raise the material temperature use. The thermodynamics of mixing, morphology, microrheology and some mechanical properties of the binary and ternary blends were studied. The results showed that there is a certain degree of affinity between PCL and PVB and between PVB and EVA. The ternary blends showed core-shell morphology with EVA probably being the core phase and PVB the shell. PVB showed a formation of co-continuous fibrillar morphology in the PCL. There was agreement with the Palierne equation only for PCL/EVA blend. Because they have a probable co-continuity formation (PCL/PVB), processing degradation (EVA/PVB) and core-shell structure, these samples deviated significantly from what was predicted by Palierne. The tensile properties of the ternary blend, with high fractions of dispersed phases - 50%, did not undergo significant changes and the impact properties significantly improved related to the PCL. Thus, the proposed ternary blend has good evidence to be used in the manufacture of orthoses due to its mechanical properties and significant cost reduction with the high fraction of the proposed dispersed phases.